The Relationship Between Physical Activity and Menstrual Cycles in Urban Adolescents Girls - Amelia, Dessy; Novembriani, Rizqie Putri; Puriastuti, Alifia Candra; Rahmawati, Fitriana Nur; Mukharam, Khamdan; Billah, Moh.Andi Arif (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Many adolescents face barriers to physical activity due to sociocultural factors, which may deter them from engaging in regular exercise. Sedentary lifestyles typical of urban adolescents may be associated with increased menstrual irregularities due to factors such as unhealthy weight gain, stress, and poor nutrition, all of which could be exacerbated by low levels of physical activity. This study aims to determine the relationship between physical activity and menstrual regularity in urban adolescents in Malang City. Method: An institutional-based cross-sectional study was conducted on public vocational high school students in Malang City from July until August 2025. The total calculated sample size is 96 respondents. Logistic regression is used to find the relationship between dependent and independent variables. Result: Logistic regression analysis showed that the level of physical activity was not significantly associated with menstrual cycle regularity (p > 0.05 across all activity categories). The Exp(B) value for moderate activity was 1.545 (95% CI: 0.424–5.633) and for high activity was 0.800 (95% CI: 0.247–2.596), indicating no meaningful difference in the likelihood of having a regular menstrual cycle compared to the low physical activity group. Model fit testing revealed Cox & Snell R Square of 0.020 and Nagelkerke R Square of 0.027, suggesting that physical activity explained only about 2–3% of the variation in menstrual cycle regularity. Conclusion: Therefore, physical activity level cannot be considered a significant predictor of menstrual cycle regularity in this study.